Public Money for Private Infrastructure : Deciding When to Offer Guarantees, Output-based Subsidies, and Other Fiscal Support - Irwin, Timothy (Washington, DC: World Bank, 2013)
When governments seek private investment in infrastructure projects, they usually find themselves asked to provide grants, guarantees, or other forms of fiscal support. Often they prefer to provide support in ways that limit immediate cash expenditure but sometimes generate large costs later. Seeking to provide support without any immediate spending of cash, for example, governments often agree to shoulder project risks and sometimes encounter fiscal problems later. For example, in the 1970s and 1980s in Spain, the government was obliged to pay $2.7 billion when the exchange-rate guarantees it had given private toll roads were called (Gomez-Ibanez 1993). More recently, the Indonesian government agreed to pay $260 million as a result of its agreements, through the electricity company it owns, to bear demand and foreign-exchange risks in private power projects. Yet even when governments have chosen to provide cash subsidies they have not always achieved their apparent goals: for example, over 80 percent of the Honduran government's "lifeline" electricity subsidies go to customers who aren't poor (Wodon et al. 2003). In still other cases, governments' decisions not to provide support may have caused problems.